Evaluating the Occurrence, Fate and Human Health Risks of Contaminants of Emerging Concern in the Atlantis Managed Aquifer Recharge Scheme - Mokhethi, Maposholi Faith (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.